اسلامی مالیاتی ادروں میں شریعہ ایڈوائزری نظام، اہمیت اور درپیش چیلنجز کا تحقیقی جائزہ: A Research Review of the Importance and Challenges of Sharia Advisory System in Islamic Financial Institutions - Ahmad, Basheer; Bashir, Hafiza Iqra (Al-Irfan, 2024)
The role of the Shariah Board in the development of Islamic financial institutions is not hidden from anyone, because they are the backbone of Islamic financial institutions. The result of this is that today the Islamic economic system in our country is going through a good phase and is on the path of development, yet some reforms are also needed in the Shariah Board for transparency in the Islamic financial system so that give us more better results. Therefore, the Shariah Board has a lot of services and a key role in the development of Islamic financial institutions, therefore, in this article we will present, the importance of the Shariah Board, its character, attributes, review of the Shariah governance with respect to the Shariah Board and the challenges faced by them in the current era, etc. so that make the Islamic financial system further strengthened. It should be improved by further development.